Pengaruh Physical Evidence dan Gaya Hidup Terhadap Loyalitas Pelanggan Pada Chanel Distro Di Tenggarong - Sadiyah, Halimatus; Palinggi, Yonathan; Adawiyah, Raudatul (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract :The aim of this research is to know whether Pshycal Evidance and Life Style Influence Simultaneously on Customer Loyalty In Chanel Distro In Tenggarong, to know whether Pshycal Evidance And Lifestyle Affects Partially To Customer Loyalty In Chanel Distro In Tenggarong and to know from both variables, which is the most dominant influence Customer Loyalty In Chanel Distro In Tenggarong. In the data analysis, in accordance with the object of research to determine the magnitude of the influence of Pshycal Evidance And Lifestyle to customer loyalty is with the model of multiple regression analysis with the help of SPSS For Window 20.0. Result of calculation of test of F (simultaneous correlation / together), obtained F count bigger than F table (Fhitung 25,227> Ftabel 3,13), so it can be said physical evidence variable and lifestyle simultaneously (able to show its effect on customer loyalty. Then the first hypothesis that "the variable of physical evidence and lifestyle have influence simultaneously to customer loyalty at Chanel Distro In Tenggarong" accepted and proven correctness. From both result of partial correlation test seen physical physics variable value which is bigger than its influence of lifestyle variable, so variable physical evidences is the most dominant variable influence to customer loyalty. From the description, it can be concluded that the third hypothesis in this study "That the physical evidence variable has a dominant influence on customer loyalty in Chanel Distro In Tenggarong" received and proven true.Â Keywords: Physical Evidence, Lifestyle, Loyalty